Post-operative rehabilitation following posterior cruciate ligament reconstruction on manual labourer - S., Priya; A., Nimmy; J., Kusuma G. (International Journal of Research in Medical Sciences, 2025)
Injuries to the posterior cruciate ligament (PCL) are less common than injuries to the anterior cruciate ligament (ACL), but they make the knee much less stable and functional. Post-operative complications such as stiffness, muscle inhibition, and gait dysfunction often require an intensive and structured rehabilitation program. This case study highlights the role of comprehensive physiotherapy following delayed PCL reconstruction and medial meniscus repair. A 32-year-old male was done with imaging after his motorcycle accident, it revealed that a near-complete PCL tear, medial meniscus tear. He underwent arthroscopic PCL reconstruction and meniscus repair followed by 3 months immobilized in a brace at 30-degree flexion. After that the patient came with a complaint of a swelling, reduced range of motion (ROM), muscle wasting, inability to flex or extend his left knee. The patient went through a 12-week rehab program that included manual therapy, electrotherapy (faradic and Russian current), progressive strength training, gait training, and cryotherapy. Significant improvements were recorded over 12 weeks: pain reduced from 8/10 to 2/10 numerical pain rating scale (NPRS), active knee flexion improved from 40° to 128°, extensor lag resolved from 27° to 0°, and IKDC score increased from 40.2%/100% to 85.1%/100%. Muscle strength across the quadriceps, hamstrings, and gluteal muscles also showed notable gains while achieving all the short- and long-term goals. This case illustrates the importance of delayed referral, week-wise rehabilitation, and individualized physiotherapy for optimal recovery following PCL reconstruction. The integration of neuromuscular stimulation, targeted strengthening, and functional re-training proved effective in restoring joint mechanics and return to daily activities. Delayed mobilization and immobilization complications underscore the need for timely, evidence-based rehabilitation protocols.